The problems and challenges of reaction research - Paužaitė, S. (Psichologija, 1968)
Currently, experimental and engineering psychology often analyzes simple sensory and motor reaction and selection reaction. Features of motion are not examined while researching these reactions; rather, most movements are heavily simplified. There are control operations requiring precise movement control. It is necessary to examine the motion structure for sustainable functioning of the management systems, which require accurate and continuous regulation and determination of the impact of various factors regulating reaction features. Experimental research of people’s regulated reactions can yield material allowing us to understand their mechanisms and regulation principles.